Translation Strategies of Subtitling Java Heat Movie - Aldo Elias Alrisky Pasaribu; Masitowarni Siregar; Meisuri (LingLit Journal Scientific Journal for Linguistics and Literature, 2022)
The objective of this study is to explain the reason of utilizing translation strategies in JavaHeat subtitling. The research methodology used in the research is qualitative research design. The objective of this study is to explain the reason of utilizing translation strategies in JavaHeat subtitling. The research methodology used in the research is qualitative research design. There were eight types of translation strategies based on Baker’s theory in Java Heat movie namely translation by paraphrase using a related word (23.32%), followed by translation by omission (19.69%), translation by illustration (16.06 %), translation by a more general word (13.95%), translation by paraphrase using unrelated words (13.95%), translation by cultural substitution (8.79%), translation by using a loan word (3.44%), and translation by a more neutral/less expressive word (0.76%).